LA CONSTRUCCIÓN DE NUEVAS IDENTIDADES FEMENINAS A TRAVÉS DE LA HISTORIETA: LA APORTACIÓN DEL MANGA SHŌJO GALS! - Bárbara FERNÁNDEZ GARCÍA (Fonseca, Journal of Communication, 2023)
In 2002 is published in Spain the shōjo manga (aimed at a young female audience) Gals!, work of the author Mihona Fujii,considered one of the best documents to know and understand the phenomenon of urban tribe of Japanese gals. This paper aims to show the realism with which it is approached fiction presented, combined with the own manga mechanisms which should be disclosed and, after thorough analysis of the main characters (all female), finding their artistic values, and how through its main protagonist proposes a new model of female character reinforced by a peculiar protagonic position, relieved of the burden of the conventional functions of the protagonist. It aims to contribute to the still scarce Spanish studies in this area.